Intracyclic speed fluctuations of the center of mass and its relationship with the index of coordination - a pilot study - Figueiredo, P.; Contreras, G.; Morales, E.; Pereira, S.; Goncalves, P.; Arellano, R.; Seifert, L.; Chollet, D.; Vilas-Boas, J. P.; Fernandes, R. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to analyse the relationship between the intracyclic speed fluctuations (dv) of the center of mass (CM), in the x,y,z axes, and the Index of Coordination (IdC), as well as to assess the general stroking parameters during the 200 m front crawl event. A good level male swimmer performed the 200 m front crawl at maximum intensity, being video taped by six cameras (2 above and 4 under the water). One complete stroke cycle was analysed in each 50 m of the 200 m test, using the APASystem (Ariel Dynamics Inc). IdC appeared to be well related to dv, both in the horizontal and vertical axes. It was also observed, during the 200 m effort, that the IdC, dv, stroke rate and stroke length changed during the exercise